Design process of a compact Tri-Band MIMO antenna with wideband characteristics for sub-6 GHz, Ku-band, and Millimeter-Wave applications - Abdullah Al-Gburi, Ahmed Jamal; Ali, Ayyaz; Bhatti, Farooq Ahmed; Munir, Mehr E; Nasralla, Moustafa M.; Esmail, Maged A. (Ain Shams University, 2024)
This article proposes a tri–band Multiple Input Multiple Output (MIMO) antenna operating at 5.2 – 5.7 GHz (5G Wi–Fi), 11.8 GHz – 17.3 GHz (Ku–band), and 23.4 GHz – 37.3 GHz (5G millimeter–Wave) frequency bands. The proposed MIMO antenna consists of a 2 × 2 configuration with a defective ground structure on Rogers–5880 substrate. An innovative passive decoupling structure, featuring thin microstrip lines positioned between the radiating elements, has been meticulously engineered to ensure a high level of isolation, achieving values of less than −20 dB. The peak gain of the MIMO antenna is found to be 3.05 dB, 5.27 dB, and 6.97 dB at 5.5 GHz, 17 GHz, and 35.5 GHz frequency bands, respectively. Measured ECC is less than 0.007, and DG is greater than 9.96. The radiation efficiency is above 90 %, TARC is less than –10 dB and channel capacity loss is below 0.4 Bits/s/Hz in all the bands of operation. The simulated and measured results are found to be in good agreement and the proposed MIMO antenna offers numerous advantages, including extensive frequency coverage, broad bandwidth, exceptional isolation, high gain, and efficiency. Consequently, it emerges as a promising choice for devices operating in Sub-6 GHz, Ku-band, and millimeter-wave applications.